Hello,

I have the following:

$\displaystyle A(x)=(x+1) + \frac{1}{2x^{2}-3x+1}$

How do I find a sequence $\displaystyle a_{0},a_{1},a_{2},...$ such that $\displaystyle A(x)=\sum_{i=0}^{\infty} a_{i}x^{i}$

Thanks.

Printable View

- Sep 21st 2011, 01:02 PMsurjectivesequence
Hello,

I have the following:

$\displaystyle A(x)=(x+1) + \frac{1}{2x^{2}-3x+1}$

How do I find a sequence $\displaystyle a_{0},a_{1},a_{2},...$ such that $\displaystyle A(x)=\sum_{i=0}^{\infty} a_{i}x^{i}$

Thanks. - Sep 21st 2011, 01:09 PMalexmahoneRe: sequence
- Sep 21st 2011, 01:31 PMsurjectiveRe: sequence
Could you elaborate a bit. It's not quite clear. I mean, when expanded how do I include x+1 ?? Assistance would be appreciated!!!

- Sep 21st 2011, 01:49 PMalexmahoneRe: sequence